Review Artikel: Hubungan Antara Tingkat Pengetahuan terhadap Perilaku Penggunaan Antibiotik Secara Rasional pada Masyarakat - Shafa Qotrunnada Widyatamaka; Indah Laily Hilmi; Salman Salman (Journal of Pharmaceutical and Sciences, 2023)
Antibiotics are a class of drugs that have a role in treating infections caused by bacteria. Inaccurate use of antibiotics can result in antibiotic resistance. A good level of knowledge will affect behavior so that the actions taken are more directed. This study aimed to determine the relationship between the level of knowledge on the behavior of using antibiotics in society. This study uses a systematic literature review method by selecting 11 interrelated journals and discussing the same topic. The results obtained are the knowledge of the behavior of using antibiotics in the community with a relationship. The community needs to increase knowledge about the use of antibiotics to optimize antibiotic use behavior, know the side effects, dosage, use and how to store antibiotics themselves and reduce the occurrence of antibiotic resistance in the community.